The Sunni-Shi'a Divide : Islam's Internal Divisions and Their Global Consequences - Betts, Robert Brenton (Book collections on Project MUSE., 2013)
Until the attacks of September 11, 2001, few Americans knew anything about Islam, let alone about the distinctions between Sunni and Shiaea, the Sufi and Wahhabi, the origins of the Holy QurAEan and Shariaea law, and the respect that all Muslims, even secular ones, harbor for the prophet Muhammad, his family, and Islamic traditions. In The Sunni-Shiaea Divide Robert Betts traces the tortuous history of IslamAEs sectarian divisions, emphasizing the most important one, the Shiaea departure from Sunni ôorthodoxy.ö. Although the majority of Muslims remain faithful to the Sunni sect of Islam, approximately 15 percent subscribe to the Shiaea creed. As AmericaAEs involvement in the Middle East drags on, Betts reiterates that policymakers, scholars, and laymen alike must understand the many faces of Islam, the internal forces in the United States that have brought us into these conflicts, and the role of Israel in the regionAEs escalating tensions. How the increasing hostility between the two main Islamic factions plays out on the world stageuas Sunni Turkey, Shiaea Iran, and their allies vie for dominanceuis of major consequence for everyone, especially financially strapped Europe and the United States.